The Birth of East-Belgian Identity and the Treaty of Versailles. A Critical Legal Analysis - Vanhullebusch, Matthias (Nationalities Papers, 2025)
„In the former districts of Eupen and Malmedy, present-day East-Belgians, in particular academic and socio-political elites, draw their collective identity, amongst others, from the historical injustices inflicted upon them ever since the adoption of the Treaty of Versailles. The transfer of sovereignty from Germany to Belgium was then the subject of a popular consultation organised by the transitional Belgian authorities in those territories. Favouring national over popular sovereignty, those authorities de facto undermined the freedom of choice and imposed their annexation to Belgium which the League of Nations, despite criticisms, consecutively endorsed. Much has been said about this petite farce belge yet not from a legal point of view. Thus, this article sheds a different light on the historical accounts of those events which are instrumentalised to construct the contemporary collective identity of the German-speaking Community of Belgium.“
Keywords: Identität; Nationalismus; Versailler Vertrag (1919)

„A trip organised for children is not a serious matter“? Summer treatment camps for the Belgian-German borderlands (1919–1939). - Venken, Machteld (Childhood, 2025)
„Although the children whose rural homelands transitioned from German to Belgian state sovereignty following the First World War were not the typical demographic targeted for preventive air treatments against tuberculosis, they were overrepresented in treatment camps in both Belgium and Germany. Nation-state representatives provided public and private (although partly state subsidized) treatment camps to restore the physical vitality, ethical integrity, and national allegiances of the minors. The parallel competitive offer took the form of a cross-border mixed economy of child welfare. Borderland residents either opportunistically supported the Belgian or German initiatives, or provided their own alternatives to protect their children from indoctrination.“
Keywords: Heilanstalt; Jugend; Kind; Nationalbewusstsein; Nationalismus; Nationenbildung; Verschickung

Nationalization campaigns and teachers’ practices in Belgian–German and Polish–German border regions (1945–1956) - Venken, Machteld (Nationalities Papers, 2014)
Keywords: Belgien; Bildungswesen; Deutschland; Eupen-Malmedy; Lehrer; Nationalismus; Polen; Schule; Sprachpolitik